Pengaruh Viral Marketing, Quality Product Dan Brand Experience Terhadap Keputusan Pembelian Pada Produk Glad2Glow (Studi Kasus Pada Mahasiswa Manajemen FEB Universitas Islam Malang 2020) - Afkarina, Izzah; Rachma, N.; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The research aims to analyze the influence of Viral Marketing, Product Quality, and Brand Experience on Glad2Glow Product Purchasing Decisions among FEB Management students at the Islamic University of Malang Class of 2020. This research uses quantitative methods with a total of 84 students as respondents. Data collection uses a questionnaire distributed via Google Form. The questionnaire consists of three variables, namely Viral Marketing, Product Quality and Brand Experience. Data analysis using SPSS, research results show that 1) Viral Marketing has a significant influence on purchasing decisions, 2) product quality has a significant influence on purchasing decisions, 3) brand experience has a significant influence on purchasing decisions. Keywords: Viral Marketing, Product Quality, Brand Experience